Successful Management of Biliary Ascariasis in a High-Endemic Zone and Low-Resource Setting in Ethiopia - Yonathan Aliye Asfaw; Girum Tesfaye Asrat; Tesfanew Bekele Uddo; Bethlehem Aliye Asfaw; Ayush Anand; Helen Huang; Eden Demessie Firew; NagaSpurthy Reddy Anugu (Case Reports in Infectious Diseases)
Ascariasis lumbricoides is a roundworm that causes one of the most common soil-transmitted helminth infections worldwide. Ascariasis is typically found in the jejunum and transmitted through the intake of Ascaris lumbricoides eggs through food and water. Initially, ascariasis can cause pulmonary symptoms during the first 6–8 weeks of ingestion and can progress to serious complications of intestinal obstruction and hepatobiliary manifestations. Biliary ascariasis is a complication of ascariasis migration from the jejunum to the hepatobiliary tree and can present with a variety of symptoms ranging from biliary colic to more serious features such as acute cholangitis. Though the mortality rate is low, limited resources for management can make it challenging to manage.